STRUCTURING THE PROFESSIONAL SKILLS SYSTEM SELF-ORGANIZATIONS OF THE FUTURE TEACHER - N.Yu. Dudnik (Academy of Cognitive and Natural Sciences, 2009)
The article deals with the question of classification of skills of professional self-organizing and their role in professional becoming of the future teachers.